A light scattering study of the kinetics of the sol-to-gel transition in particulate systems - Ebini, Raiya Husein (Kansas State University, 2020)
We present investigations of the kinetics of the colloidal sol-to-gel transition by combining small angle static light scattering (SASLS), dynamic light scattering (DLS) techniques, and transmitivity measurement. Our choice of dilute monomer volume fraction allows for a full investigation of the gelation to obtain all possible kinetic regimes. Our data verify the predictions of a kinetic theory, the ideal gel point (IGP) theory, where three regimes of kinetics are expected. We observe the first regime, the well-known cluster-dilute regime, with a kinetic exponent of z = 1, a cluster-dense regime with an enhanced kinetics and z ≃ 2, and finally, a gelation regime is observed where the aggregate growth slows and ceases to grow at the IGP predicted size, R[subscript g],G. The time from the onset of aggregation to the gelation point, the gel time t[subscript gel], has also been investigated. The scaling behavior of t[subscript gel] with the initial monomer volume fraction, f[subscript vm], and the stability ratio, W, was verified with the prediction provided by the kinetic description of gelation. It was important throughout this work to realize that the fractal dimension, D[subscript f], of the aggregates that grow to form the gel is a function of W. For that we designed a procedure that proved viable in our analysis. These results quantitatively verify the IGP theory and when combined with previous studies lead us to access the roles of thermodynamics, percolation and kinetics. We conclude that kinetics provides a complete theory of the gelation process from sol to percolated gel.
Keywords: Aggregation; Gelation; Sol-to-gel transition; Light Scattering; Kinetics of gelation; gel time